Tourism Promotion Strategy at Juanda International Airport Surabaya to Build Destination Image Through Air Transportation - Karimatun Nisak; Kartika Fajar Nieamah; Setyamartana Parman (Jurnal Flight Attendant, 2025)
Juanda International Airport in Surabaya is a gateway for tourists traveling to destinations in East Java. An extensive promotional strategy can attract large numbers of tourists, impacting the air transportation sector and the economies of communities surrounding tourist areas. This greatly influences the image of tourist destinations and the achievement of the right market targets. This study aims to identify the promotional strategies employed by Juanda International Airport to promote tourism growth and foster a positive destination image through air transportation. The research method used in this study is a qualitative approach. Previously, the author conducted an observation at Juanda International Airport in Surabaya using a structured interview method designed according to the research indicators and a photo study as a data collection technique. This study uses the SWOT analysis technique to develop new strategies. A study of tourism promotion strategies at Juanda International Airport in Surabaya indicates that strengthening tourism promotion through social media is essential. Tourist Information Centers (TICs) play a key role in helping tourists find and choose destinations. The airport's tourism promotion activities include holding traditional events, which are well-organized thanks to the collaboration between Angkasa Pura I and the Government Cultural Office. These events provide tourists with an interesting and memorable experience as they begin their trip to East Java.